MOTIVASI MAHASISWA SOSIOLOGI FISIP UNIVERSITAS RIAU DALAM MELAKUKAN VAKSINASI COVID-19 - Friska Novalina Aritonang; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study was conducted on sociology Universitas Riau student. This study aimed to analyze student motivation levels of Covid-19 vaccination using Protection Motivation Theory that was developed by Ronald Rogers (1975). Protection Motivation Theory has fourth pillar components : perceived severity; perceived vulnerability; response effectiveness; and self-efficacy. Research is using a descriptive quantitative method and using Simple Random Sampling as sampling technique. Data collection on this research is carried out by spreading questionnaire on Google Form. The collected data has processed using Statistical Product and Service Solutions (SPSS) 25. Result of this research revealed that students motivation in Covid-19 vaccination is in the high levels and the respondent was revealed positive response on Covid-19 vaccionation. Key words : Motivation, Student Response, Vaccination